Association between lipid accumulation product and non-alcoholic fatty liver disease with normal weight: a population-based study - Shen, Lingde; Lin, Yuanfang; Chen, Weifeng; Peng, Hui (Frontiers in Medicine, 2025)
BackgroundPrevious studies have indicated that Lipid accumulation product (LAP) can serve as a predictor for various metabolic diseases. However, the relationship between LAP and Non-alcoholic fatty liver disease (NAFLD) in individuals with normal weight remains unclear.MethodsThis study involves a secondary analysis of a retrospective cohort study conducted among a Japanese population consisting of 10,391 participants with normal weight, spanning from 2004 to 2015. LAP is determined by utilizing Waist circumference (WC) and Triglyceride (TG) levels. Participants were categorized into groups based on LAP quartiles. We performed an analysis of the association between LAP and NAFLD using Cox proportional-hazard regression, smooth curve fitting, and sensitivity analyses. Prediction accuracy was evaluated using the area under the curve (AUC) analysis, sensitivity, and specificity, using Receiver Operating Characteristic (ROC) curves.ResultsThe analysis revealed a statistically significant positive correlation between LAP and normal-weight NAFLD (P < 0.01). Following adjustment for various covariates in the full models, LAP was found to be associated with NAFLD (OR = 1.06, 95% CI: 1.04–1.08, P < 0.001). Sensitivity analysis was conducted by categorizing LAP as a quartile variable, showing that the top quartile had a 354% increased risk of NAFLD compared to the bottom quartile in the full model (OR = 4.54, 95% CI: 2.83–7.3, P < 0.001). A non-linear relationship was observed between the LAP and normal-weight NAFLD, with an inflection point identified at a LAP value of 12.6.Furthermore, ROC curve analysis demonstrated that LAP (AUC = 0.809, sensitivity = 83.3%, specificity = 64.7%) had superior predictive accuracy for normal-weight NAFLD compared to Body mass index (BMI) and WC.ConclusionOur study reveals a non-linear association between the LAP and the risk of NAFLD in individuals of normal weight, with LAP demonstrating superior predictive accuracy compared to BMI and WC. These results advocate for the use of LAP thresholds to guide early lifestyle interventions during metabolically reversible stages and to improve the identification of high-risk lean individuals who may be overlooked by current BMI-based screening methods.